Výskyt pozdní hematogenní infekce kloubních náhrad v nasem souboru a návrh systému prevence - Jahoda, D; Nyc, O; Simsa, J; Kucera, E; Hanek, P; Chrz, P; Pokorný, D; Tawa, N; Landor, I; Sosna, A (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2007)
PURPOSE OF THE STUDY: To design a prophylactic strategy for late hematogenous infection is not an easy task. It requires the assessment of risk factors for the patient as well as of a potential source of bacteremia. Cost effectiveness, efficacy of the antibiotic selected and complications associated with antibiotic treatment, such as allergic reactions and development of resistance to the antibiotic given, should also be considered. The aim of this retrospective study is to evaluate the occurrence of late hematogenous infection in our large group of patients, to analyze risk factors and to suggest an optimal system of antibiotic prophylaxis in order to prevent the development of this unwelcome complication. MATERIAL AND METHODS: Since our objective was to include a large number of patients, a retrospective study was chosen as the method used. The patients treated for infectious complications of total joint replacement at the 1st Department of Orthopaedics, Teaching Hospital in Motol, 1st Faculty of Medicine, Charles University, in the years 1991 through 2004, were evaluated with the use of a targeted questionnaire and complete medical records. The group comprised 229 patients, 149 women and 80 men. Of these, 123 were treated for infection of total hip replacement, 102 for total knee replacement, two had infection of prosthetic shoulder joints and two had infection of elbow joint alloplasty. RESULTS: Medical history of 37 patients (16.3 %) included infection of or a risk-associated procedure on the urogenital system (endoscopic or open surgery, prostate gland biopsy, extracorporeal lithotripsy). Six patients (2.6 %) underwent surgery with possible bacteremia (intestine resection for tumor, 2x; surgery for paronychium, 2x; cholecystectomy, 1x; and appendectomy, 1x). Dental surgery or mouth disease was recorded in 11 patients (4.8 %). DISCUSSION: The authors suggest that the orthopedic surgeons performing joint replacement should assume their deal of responsibility and should provide relevant, comprehensive information to both the patient and the attending physician. These surgeons should be ready to remain involved in their patients' further therapies and, after assessing all risks, should be able to recommend an optimal prophylactic treatment. The introduction of a new preventive approach requires a simple and uncomplicated scheme. Any complicated and expensive system of preventive antibiotic administration will only meet with lack of understanding and with trivialization. The requirement that antibiotic treatment should be selected according to the site and type of risk-associated disease is logical, but, in our opinion, rather formal and unrealistic. The authors prefer a simple system permitting a rapid and overall introduction of preventive measures. CONCLUSIONS: The groups of patients indicated for prevention of late hematogenous infection of prosthetic joints are clearly defined and, by no means, do they involve all patients with total joint replacement. Key words: prosthetic joint, infection, prevention, antibiotics, complication.
Keywords: protézy kloubů; Joint Prosthesis; mužské pohlaví; Prosthesis-Related Infections; ženské pohlaví; Humans; Female; infekce spojené s protézou; Preoperative Care; antibiotická profylaxe; Antibiotic Prophylaxis; předoperační péče; lidé; Male